Cultivating Green Human Resource Management (GHRM) to Small and Medium-Sized Enterprises (SMEs) for Green Performance - Theresia Marditama; Mohd Yusoff Yusliza (Greenation International Journal of Tourism and Management, 2023)
At the present time in Indonesia, businesses that fall into the category of "small" or "medium" might employ a sizable workforce. It is necessary to establish policies and strategies to overcome the obstacles to entry into export markets, such as local regulations and a lack of knowledge about the varying demands of export markets, even if many different types of SME products have the potential to become high-quality exports. Therefore, in order to address this problem, this article presents a literature analysis on Green Human Resource Management (GHRM) for SMEs to improve their green performance. This paper presents a comprehensive assessment as a model for professional development in light of the constraints of the existing HR development procedures in Indonesian MSMEs. This article draws the conclusion that GHRM has an opportunity to encourage green performance in Indonesian SMEs in accordance with the national business objectives of decision makers after analyzing the current practice of GHRM development in Indonesia MSMEs with national and international practices reported in the published literature. Given HRM's potential as a model for effective and sustained HRM professional development, especially in the context of SMEs in Indonesia, due to its empowering qualities in terms of both its content and its structure.